2018
DOI: 10.2478/amma-2018-0022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Food on the Pharmacokinetics of Gliclazide 60 mg Modified Release Tablet in Healthy Caucasian Volunteers

Abstract: Objective: To evaluate the food effect on glicazide disposition in clinical trials conducted on healthy Caucasian volunteers who were given a new modified release oral formulation of Gliclazide 60 mg developed by Sun Pharmaceutical Industries, India.Methods: The studies were designed as open-label, randomized, single-dose, crossover studies that consisted of two periods. During each study, venous blood samples were taken before and after drug administration up to 96 hours. Subsequently, individual plasma profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Thus, the relative fraction absorbed of gliclazide from the site of administration over time was obtained and is depicted in Figure 2. The data of the bioequivalence studies were previously reported [11,14,15]. In vitro studies By using the methodology and sample preparation described in the experimental section, the percent of dissolved gliclazide from the 60 mg modified release generic tablets were obtained, in three distinct dissolution media.…”
Section: In Vivo Datamentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the relative fraction absorbed of gliclazide from the site of administration over time was obtained and is depicted in Figure 2. The data of the bioequivalence studies were previously reported [11,14,15]. In vitro studies By using the methodology and sample preparation described in the experimental section, the percent of dissolved gliclazide from the 60 mg modified release generic tablets were obtained, in three distinct dissolution media.…”
Section: In Vivo Datamentioning
confidence: 99%
“…In vitro -in vivo correlation The in vitro-in vivo correlations (IVIVCs) were evaluated for level A correlation. Hence, the absorption profiles of Gliclazide 60 mg modified release tablets manufactured by Ranbaxy Laboratories Limited, now Sun Pharmaceutical Industries Limited, India, were obtained from the individual plasma drug concentration versus time profiles from the bioequivalence trials [11,14,15]. The absorption profiles were determined for both clinical trials performed under fasting or fed conditions.…”
Section: In Vivo Datamentioning
confidence: 99%
See 3 more Smart Citations